Miscues in Reading Aloud: Insights into Proficient and Less Proficient Readers - Ridhatillah, Muhammad Faris; Fitrisia, Dohra (Universitas Teuku Umar, 2025)
The purpose of this study is to determine the miscue that was frequently produced among good readers and poor readers. This study was limited to six students of 11th grade students in Babun Najah Islamic Boarding School using the purposive sampling method. This is a descriptive qualitative study using the of miscue analysis from Argyle (1989) and Mahmud and Gopal (2018). The findings revealed that the miscues were frequent by all readers but substitution and hesitation were the most common miscues among the subjects, with the 340 (63%) and 82 (15%) occurrences, respectively. Other miscues included repetition (58 occurrences,11%), correction (41 occurrences, 8%), insertion (17 occurrences, 3%), and omission (2 occurrences, 0%). These results highlight the prevalence of miscue patterns across different reading proficiency levels. Finally, this study will be useful as a reference for an alternative teaching strategy for English learning, especially in the course of reading. Keywords: EFL Students, Miscue Analysis, Reading Aloud